Effect of Enhancing Factor on The Developmental Resistance of Pseudaletia separata Larvae Orally Inoculated with Pseudaletia unipuncta Nucleopolyhedrovirus - Arman Wijonarko; Hamano Kunikatsu (Jurnal Perlindungan Tanaman Indonesia, 2005)
Larvae of lepidopteran insect become increasingly resistant to baculovirus infection as they age. The mechanism for this resistance is not known yet, but the phenomenon does not occur when an enhancing factor was added to the viral inoculum. This observation indicated that the mechanism of resistance occur during primary infection within midgut. By assessing the fusion of positive microvillus cell using flow cytometer, we indicated that enhancing factor may somehow help the virus to fuse in the midgut of older insect.